Compound heterozygous mutations in FBN1 in a large family with Marfan syndrome. Issue 3 (16th January 2020) - McInerney‐Leo, Aideen M.; West, Jennifer; Wheeler, Lawrie; Leo, Paul J.; Summers, Kim M.; Anderson, Lisa; Brown, Matthew A.; West, Malcolm; Duncan, Emma L.
Abstract: Background: Marfan syndrome (MFS) is a dominant monogenic disorder caused by mutations in fibrillin 1 ( FBN1 ). Rarely, compound heterozygosity for FBN1 mutations has been described. Methods: A large kindred with MFS was assessed clinically over decades, and genetically using exome and/or Sanger sequencing. Results: A previously identified FBN1 missense variant (p.Tyr754Cys) was confirmed in all subjects with MFS. An additional variant (p.Met2273Thr), previously associated with incomplete MFS, was identified in three siblings. These three compound heterozygous individuals had aortic dilatation at early age (all <30 years): one also had cerebral and ocular aneurysms; and one, who had undergone surgical repair aged 18 years, died from aortic dissection at 31 years. In contrast, their heterozygous father (p.Tyr754Cys) with MFS died at 57 years (myocardial infarction) without requiring surgical intervention and one heterozygous (p.Tyr754Cys) sibling has aortic dilatation presenting >40 years but not requiring surgical intervention. Another heterozygous (p.Tyr754Cys) sibling did require aortic root repair (28 years). The heterozygous (p.Met2273Thr) mother had aortic dilatation diagnosed at age 68 years but has not required surgical repair. Conclusion: Although compound heterozygosity or homozygosity is rare in MFS, it should be considered when there is an unusually severe phenotype in a subset of family members. Abstract : Marfan syndrome (MFS) is a dominant monogenic disorder caused by mutations in FBN1. Compound heterozygous mutations in FBN1 were identified in a large family with Marfan syndrome. Although compound heterozygosity or homozygosity is rare in MFS, it should be considered when there is an unusually severe phenotype in a subset of family members.